Incidence of appendicitis and ovarian cyst among female patients presenting with acute abdomen at a tertiary care hospital - Reddy, E. Chandrasekhara; Vellanki, Janaki (International Journal of Research in Medical Sciences, 2018)
Background: Physicians working in casualty are often confronted with acute abdomen and get much more bothered as the diagnosis is not easy. This is due to the fact that the etiology of acute abdomen is always much diversified and the classical findings are masked making the diagnosis difficult. Objective was to study incidence of appendicitis and ovarian cyst among female patients presenting with acute abdomen. Methods: A hospital based follow up study was carried out among 64 cases presented with acute abdomen to the casualty from January 2018 to August 2018. All necessary investigations were done to confirm the etiology of acute abdomen. The cases belonged to surgery and gynecology departments where they were operated. The patients were followed from admission in the casualty to the final outcome. The data was analyzed using proportions. Results: During the study period a total of 15413 patients were admitted in the casualty out of them, 64 (0.42%) presented with acute abdomen. Of these 64 cases, majority i.e. 35 (54.7%) were due to acute appendicitis; 13 cases were due to renal colic and eight cases each were due to ectopic pregnancy and ovarian cyst. The most common age group affected was 21-30 years (62.5%) followed by less than 20 years age (21.9%). 25% of the 64 cases had delayed wound healing and no other complications were reported. No death was recorded. Conclusions: Authors achieved excellent results as there were no major complications and no death was recorded. Thus, meticulous diagnosis and prompt treatment can save patient life and at the same time rate of complications can be reduced.